2014
DOI: 10.1063/1.4903000
|View full text |Cite
|
Sign up to set email alerts
|

SU(4) based classification of four-level systems and their semiclassical solution

Abstract: We present a systematic method to classify the four-level system using SU (4) symmetry as the basis group. It is shown that this symmetry allows three dipole transitions which eventually leads to six possible configurations of the four-level system. Using a dressed atom approach, the semiclassical version of each configuration is exactly solved under rotating wave approximation and the symmetry of the Rabi oscillation among various models is studied and its implication is discussed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In particular, it is shown that for some specific pairs of Bell states, the model precisely recovers the collapse and revival time of typical JCM at each local sites. Going beyond multifaceted applications of photonic entanglement, the study of the entanglement scenario of atomic or molecular system with two or three levels 38,39 has a very special appeal as they are connected with plethora of quantum-optical phenomena such as, intensity-intensity correlation, squeezing phenomenon, Moller splitting, bunching and anti-bunching effect etc 41 including the manipulation of the bulk properties of materials such as EIT 43 . Studies of the diverse class of bipartite system within the framework of the D-JCM may provide a handle to explore a new arena of quantum correlation where the manipulation and control of various optical properties could be done nonlocally.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, it is shown that for some specific pairs of Bell states, the model precisely recovers the collapse and revival time of typical JCM at each local sites. Going beyond multifaceted applications of photonic entanglement, the study of the entanglement scenario of atomic or molecular system with two or three levels 38,39 has a very special appeal as they are connected with plethora of quantum-optical phenomena such as, intensity-intensity correlation, squeezing phenomenon, Moller splitting, bunching and anti-bunching effect etc 41 including the manipulation of the bulk properties of materials such as EIT 43 . Studies of the diverse class of bipartite system within the framework of the D-JCM may provide a handle to explore a new arena of quantum correlation where the manipulation and control of various optical properties could be done nonlocally.…”
Section: Discussionmentioning
confidence: 99%
“…For Scenario-I, to solve the D-JCM using the dressed state formalism, we define the initial dressed wave function by a orthogonal transformation of the bare state in Eq. ( 9) 37,39 ,…”
Section: Dressed State Solution Of Double Jaynes-cummings Modelmentioning
confidence: 99%
See 1 more Smart Citation